1995
DOI: 10.1002/j.1460-2075.1995.tb00095.x
|View full text |Cite
|
Sign up to set email alerts
|

tRNAs are imported into mitochondria of Trypanosoma brucei independently of their genomic context and genetic origin.

Abstract: The mitochondrial genome of Trypanosoma brucei does not encode any identifiable tRNAs. Instead, mitochondrial tRNAs are synthesized in the nucleus and subsequently imported into mitochondria. In order to analyse the signals which target the tRNAs into the mitochondria, an in vivo import system has been developed: tRNA variants were expressed episomally and their import into mitochondria assessed by purification and nuclease treatment of the mitochondrial fraction. Three tRNA genes were tested in this system: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Evidence that specific RNA import in trypanosomatids is achieved by the presence of antideterminants within nonimported tRNAs is less direct, but intriguing. In Trypanosoma brucei, tRNAs from yeast and human as well as mutants of T. bruceiimported tRNAs all exhibit some mitochondrial localization when expressed from nuclear genes (Hauser and Schneider 1995). This led to the conclusion that no specific signals were required to achieve tRNA import in this organism, but that the tRNA structure alone was sufficient to direct import (Hauser and Schneider 1995), a conclusion consistent with the proposed idea.…”
Section: Rna Import Signals In Other Organismssupporting
confidence: 59%
See 1 more Smart Citation
“…Evidence that specific RNA import in trypanosomatids is achieved by the presence of antideterminants within nonimported tRNAs is less direct, but intriguing. In Trypanosoma brucei, tRNAs from yeast and human as well as mutants of T. bruceiimported tRNAs all exhibit some mitochondrial localization when expressed from nuclear genes (Hauser and Schneider 1995). This led to the conclusion that no specific signals were required to achieve tRNA import in this organism, but that the tRNA structure alone was sufficient to direct import (Hauser and Schneider 1995), a conclusion consistent with the proposed idea.…”
Section: Rna Import Signals In Other Organismssupporting
confidence: 59%
“…Therefore, the conclusions drawn from these data regarding the role of synthetases in tRNA import may not be generalizable to the import of multiple tRNAs for use in mitochondrial translation. Perhaps more relevant to the general question of the role of synthetases in the import of tRNAs is recent work in T. brucei (Schneider et al 1994;Hauser and Schneider 1995). Using an in vivo tRNA import assay, these workers found that a mutant tRNA Tyr containing an unsplicable intron could be imported into mitochondria.…”
Section: The Potential Role Of Aminoacyl Trna Synthetases In Trna Importmentioning
confidence: 99%
“…Northern blots were done as described (17). The indicated oligonucleotides directed against the T-stem loop region were used for the specific detection of tRNA Met-i (GT-TGGTTTCGATCCAACG) and tRNA Met-e (GTGAGGCTC-GAACTCACG).…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear why all eukaryotic cells maintain separate translational apparatuses for the cytosol and the mitochondria. This situation is particularly intriguing among kinetoplastids, where only nuclear genes code for tRNAs which function indistinctively in the cytosol and in the mitochondria, but mitochondria-specific ARS still exist (12). It has been determined that at least some of the Trypanosoma and Leishmania tRNAs that are transported to the mitochondria become modified (13,14).…”
mentioning
confidence: 99%